The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/lit.12077
|View full text |Cite
|
Sign up to set email alerts
|

“Long, boring, and tedious”: youths' experiences with complex, religious texts

Abstract: Growing out of the renewed attention to text complexity in the United States and the large population of youth who are deeply committed to reading scripture, this study explores 16 Latter‐day Saint and Methodist youths' experiences with complex, religious texts. The study took place in the Midwestern United States. Data consisted of an academic year of participant observations and 59 extensive, semi‐structured interviews conducted over 2 years. Constant comparative analysis revealed two primary areas of strugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Given the importance of sacred texts and the critical relationship between sacred texts and faith development (Smith and Denton, 2005), research examining the practices religious youths use to make sense of Scripture warrants serious scholarly attention. Understanding the nature of religious youths' Scripture-reading practices may be particularly important for religious institutions because Scripture is complex, often anachronistic, and can be frustrating and difficult for youths to understand (Rackley and Kwok, 2016). Therefore, institutions must be attentive to the development of appropriate Scripture-reading practices that provide youths with the skills and opportunities to learn how to read Scripture in ways that cohere with their respective faiths and that allow youths to access Scripture in ways that support their own construction of meaning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of sacred texts and the critical relationship between sacred texts and faith development (Smith and Denton, 2005), research examining the practices religious youths use to make sense of Scripture warrants serious scholarly attention. Understanding the nature of religious youths' Scripture-reading practices may be particularly important for religious institutions because Scripture is complex, often anachronistic, and can be frustrating and difficult for youths to understand (Rackley and Kwok, 2016). Therefore, institutions must be attentive to the development of appropriate Scripture-reading practices that provide youths with the skills and opportunities to learn how to read Scripture in ways that cohere with their respective faiths and that allow youths to access Scripture in ways that support their own construction of meaning.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to language-oriented confusions, current research suggests that Methodist youths can struggle with the intratextual and personal contradictions they see in Scripture (Rackley and Kwok, 2016), both of which can limit their willingness and ability to comprehend sacred texts. Although the language confusions were more prominent than the contradictions in the present study, it is important that the youths were able to articulate when they were not understanding Scripture, regardless of the nature of their confusion.…”
Section: Recognizing Confusionmentioning
confidence: 99%
“…Some research has also intentionally addressed expanded notions of what constitutes a family, extending family literacy to include grandparents and other caregivers (Edwards & Turner, 2009; Mui & Anderson, 2008), including those who are not biologically related to the children. Additional research has explored the nature of community literacy practices among generations, looking at how community practices such as religion (Rackley & Kwok, 2016) and technology (Lewis Ellison & Wang, 2018) affect literacy development. These important studies have demonstrated that we need to think beyond parent–child interactions in home spaces to understand the significance of families’ literacy practices.…”
Section: Trauma and Family Literacymentioning
confidence: 99%
“…To the best of the authors’ knowledge, “tedious tasks” have not yet been clearly defined in the literature. Based on the description of tedious activity in previous literature 9 , 10 , we define a “tedious task” as an activity or piece of work that the processes are unnecessarily monotonous, repetitive, and time-consuming. Performing a tedious task in human–agent interaction easily leads to a negative user experience 9 , 10 , and even reduces human performance and motivation to participate in the task.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the description of tedious activity in previous literature 9 , 10 , we define a “tedious task” as an activity or piece of work that the processes are unnecessarily monotonous, repetitive, and time-consuming. Performing a tedious task in human–agent interaction easily leads to a negative user experience 9 , 10 , and even reduces human performance and motivation to participate in the task. Therefore, it is desirable to explore effective factors to improve the human experience in tedious tasks by establishing a positive human–agent relationship.…”
Section: Introductionmentioning
confidence: 99%